TEACHERS’ SENSE OF EFFICACY IN RELATION TO STUDENTS’ ENGLISH ACHIEVEMENT AT STATE ISLAMIC SENIOR HIGH SCHOOLS IN PALEMBANG - Apik Soraya; Muslih Hambali; Zuraida Siregar (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: This study was proposed to find out whether or not (1) there was a significant correlation between teachers’ sense of efficacy and students’ English achievement at State Islamic Senior High Schools in Palembang, and (2) teachers’ sense of efficacy contributed to students’ English achievement. The method used was descriptive method. The population of the research was divided into two groups. The first population was the English teachers at State Islamic Senior High Schools in Palembang. The writer used comprehensive sampling technique. There were 20 English teachers and all of them were taken as the first sample. The second was the students at the same schools with the total number 1741. The writer used purposive sampling technique. So there were 320 students taken as the second sample. The data obtained by means ready-made questionnaire (TSES) for English teachers and students’ English achievement obtained from their teachers’ documentation. TSES was completed by the teachers in order to measure their level of sense of efficacy and it was correlated to students’ English achievement. The findings showed that there was a significant correlation between the independent variable (teachers’ sense of efficacy) and the dependent variable (students’ English achievement) of this study (r = 0.797, p = 0.00). Moreover, the result of determination analysis revealed that teachers’ sense of efficacy contributed 63.5% to students’ English achievement(R = 0.797and R2 = 0.635). Key words: correlation, teachers’ sense of efficacy, students’ English achievement